PDGFR‐β and kidney fibrosis - Alberto Ortiz (EMBO Molecular Medicine)
Abstract Chronic kidney disease (CKD) is one of the fastest growing global causes of death, estimated to rank among the top five by 2040 (Foreman et al, 2018). This illustrates current pitfalls in diagnosis and management of CKD. Advanced CKD requires renal function replacement by dialysis or transplantation. However, earlier CKD stages, even when renal function is still normal, are already associated with an increased risk of premature death (Perez‐Gomez et al, 2019). Thus, novel approaches to diagnose and treat CKD are needed. The histopathological hallmark of CKD is kidney fibrosis, which is closely associated with local inflammation and loss of kidney parenchymal cells. Thus, kidney fibrosis is an attractive process to develop tests allowing an earlier diagnosis of CKD and represents a potential therapeutic target to slow CKD progression or promote regression.